Somatoform Disorders among Patients Who Visit Kampo Clinic - MURATA, Takaaki; YOROZU, Tomoko; FUKUZAWA, Motoko; ONO, Yutaka; ISHII, Koichi; OTA, Hiroaki; KANBA, Shigenobu; YAMADA, Kazuo; YAMADA, Hiroyuki; MIZUSHIMA, Hiroko; ASAI, Masahiro (Kampo Medicine, 1997)
It has been experienced that Kampo, with its philosophy that every disease is psychosomatic in origin and that herbs affect both the psyche and the soma, sometimes has a dramatic effect on somatoform disorders, though there has been no study examining the effects of Kampo on somatoform disorders. In this preliminary study, the morbidity of somatoform disorders among patients who visited the Keio Kampo Clinic and the patients' psychological well-being were examined. One hundred patients (17 males and 83 females; mean age [±SD], 39±16) who sought Kampo treatment for the first time at Keio University Hospital participated in this study. A Japanese checklist derived from the somatoform disorders schedule (version 1.1) was used to check the somatoform symptoms. To assess psychological well-being, the subjective well-being inventory (SUBI) was performed. The subjects' clinical records were examined afterwards to rule out symptoms which could be medically explained. Somatoform patients and medically ill (non-somatoform) patients were 65% and 26% of the total respectively. The somatoform patients showed significantly lower SUBI positive scores than the non-somatoform patients (p=0.042), while SUBI negative scores were significantly higher (p=0.001). Among the somatoform patients, there was a negative correlation between numbers of somatoform symptoms and SUBI positive scores (r=0.267; p=0.032), and a positive correlation between numbers of somatoform symptoms and SUBI negative scores (r=0.337; p=0.006). Following the SUBI scores through treatment courses may lead to a better understanding of the pathology of somatoform disorders and to more effective use of Kampo.